Urgensi Penetapan Wali Adhal Perspektif Maqashid Syari’ah: Studi Penetapan di Pengadilan Agama Tanjung Pati - Herawati, Rahmi (Al Muhkam: Journal of Islamic Law and Jurisprudence, 2025)
This study examined the importance of determining wali adhal by the Tanjung Pati Religious Court from the perspective of maqashid sharia. The research was motivated by cases in which a legal guardian (wali) refused to marry off a woman under his guardianship, where the reasons for such refusal were not justified under Islamic law. This refusal prompted the woman to submit a wali adhal petition to the Religious Court, as the guardian’s unwillingness to act as a marriage guardian obstructed the performance of the marriage contract and resulted in injustice toward her. To assess the urgency of the Religious Court’s determination in resolving wali adhal cases, the author conducted an in-depth analysis of a specific case decided by the Tanjung Pati Religious Court, namely case number 0041/Pdt.P/2018/PA.LK. This study employed a qualitative and descriptive research approach, using content analysis techniques and a hermeneutical approach to examine the urgency of wali adhal determination in light of the maqashid sharia framework. The findings demonstrated that the determination of wali adhal by the Religious Court played a crucial role in realizing public welfare (mashlahah) when a guardian refused to marry off a woman under his guardianship without a valid sharia-based reason. This determination safeguarded the objectives of Islamic law as articulated in the principles of maqashid sharia, namely hifzh al-nasl (protection of lineage), hifzh al-nafs (protection of life), and hifzh al-din (protection of religion)